2020
DOI: 10.1002/mame.201900796
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of β‐Phase Crystalline Structure and Piezoelectric Properties of Flexible PVDF/Ionic Liquid Surfactant Composite Nanofibers for Potential Application in Sensing and Self‐Powering

Abstract: Polyvinylidene fluoride (PVDF) is a piezo‐polymer which among its crystalline phases, the β‐phase has been researched for the improvement of piezoelectric properties. In this study, to improve the β‐phase contents and thereby the piezoelectric response of the polymer, the effect of adding self‐synthesized ionic liquid surfactant (ILS) in PVDF nanofibers is studied. This material is added in different weight percentages into the PVDF solution and the nanofibers are produced by electrospinning to prepare active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Organic nanomaterials are used as additives to improve the β phase of PVDF nanofibers in many researches, including graphene [ 85 ], carbon nanotubes (CNTs) [ 105 ], tetramethylammoniumchloride (TMAC) [ 118 ], tetrabutyl-ammonium chloride (TBAC) [ 64 , 150 ], 2,3-dihydrodecafluoropentane [ 82 ], and 1-octadecyl-3-methylimidazolium bromide ([OMD]Br) [ 97 ]. Organic nanoparticles can enhance the β phase of PVDF nanofibers, attributed to the strong interaction between organic nanomaterials and PVDF.…”
Section: Introduction Of Nanoparticles To the Structure Of Nanofibmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic nanomaterials are used as additives to improve the β phase of PVDF nanofibers in many researches, including graphene [ 85 ], carbon nanotubes (CNTs) [ 105 ], tetramethylammoniumchloride (TMAC) [ 118 ], tetrabutyl-ammonium chloride (TBAC) [ 64 , 150 ], 2,3-dihydrodecafluoropentane [ 82 ], and 1-octadecyl-3-methylimidazolium bromide ([OMD]Br) [ 97 ]. Organic nanoparticles can enhance the β phase of PVDF nanofibers, attributed to the strong interaction between organic nanomaterials and PVDF.…”
Section: Introduction Of Nanoparticles To the Structure Of Nanofibmentioning
confidence: 99%
“…Mahdavi et al added 0.25, 1, and 4 wt % of 1-octadecyl-3-methylimidazolium Bromide ([OMD]Br) to 22 wt % of a PVDF/DMF/acetone solution [ 97 ]. The results showed that the F(β) of pure PVDF nanofibers is 76.04%.…”
Section: Introduction Of Nanoparticles To the Structure Of Nanofibmentioning
confidence: 99%
“…Figure b shows the quantitative plot of α- (760 cm –1 ) and β- (1273 cm –1 ) phases with the thickness of the relative peak (TRP) calculated by previously reported studies, , and the percentage of electroactive phases ( F EA ) in PVDF with varying MNC concentrations was calculated as follows A EA and A 764 are the absorbance intensities and K 841 (7.7 × 10 4 cm 2 mol –1 ) and K 760 (6.1 × 10 4 cm 2 mol –1 ) are the corresponding absorption coefficients of 841 and 760 cm –1 peaks, respectively. , The content of the electroactive phase initially increases with the MNC weight percent up to 3 wt % and then decreases (Figure b). PVDF–MNC (3 wt %) shows 69% of F EA , higher than that of n -PVDF ( F EA = 62%), and this can be explained by the fact that during electrospinning, the local electric field in MNC increased, thus leading to an extended Coulombic force, which gives rise to the formation of a higher β-crystalline phase .…”
Section: Resultsmentioning
confidence: 99%
“…This polymer has four crystalline phases named α , β , γ , and δ respectively. The β ‐phase has the best piezoelectric response 32 . Usually the d 33 of PVDF is ∼33 pC/N which is one order of magnitude better than quartz 33…”
Section: Transducers Used In the Pasmentioning
confidence: 99%